Faktor-Faktor yang Mempengaruhi Kepatuhan ODHIV dalam Terapi ARV di Dunia Tahun 2018 - 2022 - Marlysawati, Dewi; Sudaryo, Mondastri Korib (Adi Husada Nursing Journal, 2024)
ARV therapy is important in treating HIV cases. Even though it does not cure, ARVs help suppress the growth of the virus. Adherence to therapy is essential to achieve optimal results. The objective was to decide the components that impact the adherence of PLHIV in ARV treatment. This could be a story writing audit think about conducted by looking at articles through the Science Coordinate and PubMed databases. The catchphrases utilized are Variables impacting adherence to antiretroviral treatment among HIV/AIDS patients, HIV patient adherence to ART, and "adherence" and ART HIV/AIDS patients, with inclusion criteria: Articles published in 2018-2022, published in Indonesian language or English, original research, available in full text. Exclusion criteria: articles published before 2018, review articles, and qualitative studies, do not discuss factors for adherence to ARV therapy. 20 articles satisfy the review criteria, various factors that affect adherence to ARV therapy are socio-demographic factors, clinical factors, therapeutic factors, healthcare facilities factors, and other contextual factors. Poor quality of health services, level of education, younger age, social support, community stigma, COVID-19 pandemic, and ability and understanding of ART act as risk factors for PLHIV’s adherence to ARV treatment. The discoveries of these different variables ended up reference for wellbeing offices to move forward the quality of administrations and public awareness of optimal ARV therapy adherence.